Yo tan vieja, ¿ya qué? Relaciones sexo-afectivas de lesbianas adultas mayores de Bogotá-Colombia - Fernández de Castro Peñaranda, Ana Margarita (2021)
This article analyzes the construction of the sex-affective relationships of older lesbians in Bogotá. Following the approaches of feminist gerontology and the life course, in this research I compiled the life stories of eight lesbians over sixty. This, to understand how their life trajectories affect the way they build their sex-affective life in old age. From the field work, I identify that gender and sexuality shape aging experiences of this segment. I argue that the building of sex-affective relationships and the meanings and importance attributed depend, among others, of their life courses, their current material situation, the degree of closeness to their families, their life expectations and self-perception. In addition, they are influenced by external factors such as, for example: censorship of their sexuality and the lack of spaces for lesbo-socialization designed for older women. Among these meanings and importance, I expose: the possibility of having company, affection and care, of obtaining daily sustenance and of giving continuity to their sexuality.